Hyperglobus and Pseudoptosis in Type 1 Lipogenic Thyroid Eye Disease - Amee D. Azad; Edith R. Reshef; Nahyoung Grace Lee (American Journal of Ophthalmology Case Reports, 2023)
Purpose: We present a case of Type 1 (lipogenic) Thyroid Eye Disease (TED) and our aim is to describe an atypical presentation of a rare orbital process. Observations: A man in his 50s presented with left-sided eyelid drooping. His exam showed no evidence of active inflammation but did show left hyperglobus and ipsilateral upper eyelid pseudoptosis. He had no prior history or symptoms of Graves’ Disease and imaging did not show evidence of extraocular muscle enlargement, bony asymmetries, or masses in the orbit. Subsequent lab work showed a low TSH (thyroid-stimulating hormone), elevated free T4 (thyroxine) and T3 (triiodothyronine), and elevated TSI (thyroid-stimulating immunoglobulin) index. Conclusions and importance: This is a unique and atypical presentation of a patient diagnosed with Type 1 (lipogenic) TED causing hyperglobus and pseudoptosis secondary to fat expansion in the absence of other classic TED findings such as contralateral eyelid retraction or extraocular muscle enlargement. Thyroid eye disease can have a heterogenous disease presentation, as evidenced by this case, and should always be considered in the differential diagnosis of pseudoptosis.